Challenges and Opportunities for Developing Innovative Sharia Financial Products at Bank Syariah Indonesia, Cemara Asri Branch - Anisah Cyntia Dewi Pratama; Tuti Anggraini; Ahmad Perdana Indra (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to The opportunities and challenges of creating cutting-edge Islamic financial products at Bank Syariah Indonesia (BSI) KCP Cemara Asri are examined in this study. Interviews, observations, and document analysis are the methods used to gather data for the qualitative research approach. The results of the study indicate that the main challenges in developing sharia financial products include limited sharia financial literacy in the community, complex regulations, competition with conventional financial products, and limited technological and innovation resources. However, there are great opportunities for BSI KCP Cemara Asri to develop innovative sharia financial products, including increasing public awareness of the sharia economy, government support in strengthening sharia financial regulations, and technological advances that enable the digitalization of banking services. Strategies that can be implemented include increasing sharia financial literacy, optimizing digital technology in product development, and strengthening collaboration with various parties, including sharia fintech. By overcoming existing challenges and using available opportunities, BSI KCP Cemara Asri can increase competitiveness and provide more inclusive and innovative sharia financial solutions for the community.